A systemic lupus erythematosus patient with thunderclap headache: reversible cerebral vasoconstriction syndrome. (June 2019) - Chung, S W; Lee, K M; Heo, S H; Ra, R; Hong, S -J; Yang, H -I; Lee, S -H; Song, R; Lee, Y -A
Headaches are common in patients with systemic lupus erythematosus (SLE). It is important to identify the exact cause of headaches in SLE to avoid unnecessary steroid or immunosuppressive therapy like in neuropsychiatric SLE. A 35-year-old woman with SLE suddenly developed severe headache. Magnetic resonance angiography showed multifocal segmental narrowing of cerebral arteries, suggestive of central nervous system vasculitis. However, lack of abnormal enhancement in vessel wall imaging indicated reversible cerebral vasoconstriction syndrome (RCVS) rather than central nervous system vasculitis. The patient was treated with oral nimodipine and she recovered over a period of two months. Following magnetic resonance angiography on day 90 was normal. Herein we report a case of reversible cerebral vasoconstriction syndrome in an SLE patient with literature review.